2020
DOI: 10.1002/jpen.1944
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Preoperative Short‐Term Parenteral Nutrition Support on the Clinical Outcome of Gastric Cancer Patients: A Propensity Score Matching Analysis

Abstract: Objectives: Nutrition status is of great significance to the clinical outcome after major abdominal surgery. However, the effect of preoperative short-term parenteral nutrition (PN) support among gastric cancer (GC) patients remains unknown and was evaluated in the current study. Methods: We retrospectively analyzed 455 nutritionally at-risk GC patients after radical resection from 2010 to 2016. We matched patients with 3-7 days of PN support to those without PN support. χ 2 And Mann-Whitney U tests were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
1
5
1
Order By: Relevance
“…PN did not affect long-term survival (P=0.950) regardless of whether patients were grouped according to SMI, TNM stage, or tumor differentiation. Huang et al and Xu et al demonstrated that short-term preoperative PN (3–7 days) did not significantly improve the prognosis of patients with GC at high risk of malnutrition or sarcopenia ( 21 , 22 ), which is similar to our results. We also found no significant effect of short-term preoperative PN on long-term survival (P=0.950).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…PN did not affect long-term survival (P=0.950) regardless of whether patients were grouped according to SMI, TNM stage, or tumor differentiation. Huang et al and Xu et al demonstrated that short-term preoperative PN (3–7 days) did not significantly improve the prognosis of patients with GC at high risk of malnutrition or sarcopenia ( 21 , 22 ), which is similar to our results. We also found no significant effect of short-term preoperative PN on long-term survival (P=0.950).…”
Section: Discussionsupporting
confidence: 92%
“…In addition, as opposed to EN, PN is less commonly used by surgeons because it is less incompatible with human physiology ( 6 ). Studies have shown that the prevalence of postoperative complications decreases in malnourished patients with longer preoperative PN (≥7 days) ( 9 ), whereas it did not decrease with short-term PN ( 21 , 22 ). In fact, patients receiving PN therapy are not limited to those who are malnourished.…”
Section: Introductionmentioning
confidence: 99%
“…Nutritional care is an integral component of multi-disciplinary anti-cancer treatments, and has been shown to optimize the clinical outcomes for patients with various cancers (6)(7)(8)(9) . Malnutrition frequently develops in oncology patients due to either the tumor itself or various anti-cancer treatments, and can lead to poorer clinical outcomes (6) .…”
Section: Introductionmentioning
confidence: 99%
“…Weight loss is common in people, and it can happen anywhere from 31% to 85% of the time, depending on the type of cancer. People with GC lost more than 5 percent of their weight, according to [20] [21].…”
Section: Nutrition Declinementioning
confidence: 99%
“…Quality of life is a vague term that means different things to different people. The term is still being debated today [21]. One way to think about this is to make a person important, meaningful, and happy in life.…”
Section: Quality Of Lifementioning
confidence: 99%